Strategi Pengembangan Talenta Bahasa Indonesia dalam Perspektif Manajemen Kurikulum: Studi Kasus di Universitas Guangxi Minzu - Zheng Yan; Achadi Budi Santosa; Intan Rawit Sapanti; Luo Ying (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2025)
Increased cooperation between China and ASEAN and the promotion of the Belt and Road Initiative have increased the need for graduates who are proficient in Indonesian. Guangxi Minzu University plays an important role in preparing such talent through its “3+1” learning model, which consists of three years of study in China and one year in Indonesia. This study employs an embedded mixed-methods approach, with data collected through online interviews with three lecturers from the Indonesian Language Study Program. The analysis focuses on the curriculum structure, learning model, and implementation challenges. The results show that the curriculum focuses on language skills (50%), cultural understanding (20%), and work practices (15%). However, there are still obstacles such as a lack of integration between domestic and overseas programs and minimal assessment of the learning process. The university has begun to collaborate with industry to open project classes and bring in practitioners as lecturers. This study recommends stronger curriculum integration, improvement of the evaluation system, and increased industry involvement so that graduates have better language skills, cross-cultural understanding, and work readiness in the Southeast Asian region.